Konflikty pomiędzy duchowieństwem rzymskokatolickim a greckokatolickim na terenie administratury apostolskiej kamieńskiej, lubuskiej i prałatury pilskiej w latach sześćdziesiątych XX wieku = Conflicts between the roman catholic and greek catholic clergy at the area of apostolic administration of kamieńska, lubuska, and pilska prelature in the 1960s - Woźniak, Sylwester (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The task of the article is to present how relations between the Roman Catholic and Greek Catholic Church in the Apostolic Administration with the capital in Gorzów Wlkp. were formed. Its territory included areas of Western Pomerania, north-west Wielkopolska and most of the con- temporary Lubuskie Voivodeship.
Keywords: duchowieństwo rzymskokatolickie; duchowieństwo greckokatolickie; Ziemie Zachodnie i Północne; historia kościoła; the Roman Catholic clergy; Greek Catholic clergy; Western and Northern Territories Poland; history of church